Come sostenere le fragilità genitoriali in istituzioni residenziali? - Bastianoni, Paola (Studi sulla Formazione/Open Journal of Education, 2022)
This article proposes a reflection on the educational skills of residential institutions that welcome mothers with their children following the assessment of their vulnerability in terms of parental functioning. The reflections conducted will be supported by testimonies collected in various training contexts addressed to educators of the mother/child communities and in some group meetings held with mothers whose children have been entrusted to foster families. How can the residential community that welcomes them constitute itself as a “symbolic parent” to repair those ancient wounds that have made them incomplete daughters and now “fragile” mothers? These are the questions we are going to answer.